The fall of Arthur - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; Tolkien, Christopher (Boston : Houghton Mifflin Harcourt, 2013)
The first publication of a previously unknown narrative poem by J.R.R. Tolkien, which tells the extraordinary story of the final days of England's legendary hero, King Arthur.
Foreword -- The fall of Arthur -- Notes on the text of The fall of Arthur -- The poem in Arthurian tradition -- The unwritten poem and its relation to The Silmarillion -- The evolution of the poem -- Appendix: Old English verse.
Keywords: Arthur, -- King -- Poetry; Britons -- Kings and rulers -- Poetry; Knights and knighthood -- Poetry; Arthurian romances -- Adaptations; Poetry